Multifocal CT enhancement in MS. - Ebers, G; Vinuela, F; Feasby, T; Bass, B (1984)
Review of 146 CTs in 125 MS patients showed that 53.4% (39/73) of those done during acute relapse showed enhancing lesions. Of scans done during the "active" stage of disease, 40.8% (20/49) showed enhancement, whereas only 12.5% (3/24) showed enhancement during clinically inactive periods. Autopsy confirmation that enhancing lesions represent demyelinating plaques was obtained in one patient. This study shows that enhancing lesions in MS reflect biologic activity and are most likely to be seen during acute clinically apparent relapses. More than one-half of the patients hospitalized with acute attacks appeared to be having multifocal relapses. These findings show that acute relapses are commonly multifocal and suggest that they are mediated by blood-borne factors.